Evaluación de la titulación de anticuerpos ante newcastle y bronquitis infecciosa en pollos broiler con la adición de llantén (plantago major) al 10 y 20 % en el balanceado, en la provincia Pichincha, cantón Quito - Chango Tipán, Estefanía Alexandra (2015)
In the Pichincha province, canton Quito, a study to assess the antibodies levels in the Newcastle and bronchitis infectious by llantén (Plantago major), in 10-20% balanced meal during 43 days was conducted. 90 broiler chickens from 1 day old, divided into 3 blocks with 3 treatments under a system of completely randomized blocks were used. The treatments were: to control treatment (T0) without vaccines, Treatment 1 (T1) unvaccinated + 10% Plantago major, Treatment 2 (T2) unvaccinated + 20% Plantago major….